Attitudes of Palestinian Health-Care Professionals in Gaza to Clinical Practice Guideline for Diagnosis and Treatment of Diabetes Mellitus - Radwan, Mahmoud; Akbari Sari, Ali; Rashidian, Arash; Takian, Amirhossein; Abou-Dagga, Sanaa; Elsous, Aymen (Frontiers in Endocrinology, 2017)
Background: Despite the huge numbers of the internationally produced and implemented Clinical Practice Guidelines (CPGs), the compliance with them is still low in healthcare. This study aimed at assessing the attitudes of Palestinian healthcare professionals towards the most perceived factors influencing the adherence to the CPG for Diabetes Mellitus (DM) in the Primary Healthcare centers of the Ministry of Health (PHC-MoH) and the Primary Healthcare centers of the United Nations Relief and Works Agency for Palestine Refugees (PHC-UNRWA) using a validated questionnaire Methods: A cross sectional design was employed with a census sample of all Palestinian family doctors and nurses (n=323). The Cabana theoretical framework was used to develop a study questionnaire. A cross cultural adaptation framework was followed to develop the Arabic version questionnaire. The psychometric properties of Arabic version were finally assessed. Results: The Arabic version questionnaire showed a good construct validity and internal consistency reliability. The overall adherence level to the diabetic guideline was disappointingly suboptimal 51.5% (47.3% in the PHC-MoH and 55.5% in the PHC-UNRWA) p=0.000. The most frequently perceived barriers in the PHC-MoH were lack of incentives, lack of resources, and lack of guideline trustworthiness, whereas the lack of time and the lack of guideline trustworthiness were the most prominent barriers in the PHC-UNRWA. In spite of the lack of trustworthiness of the diabetic guideline, most respondents in both settings had a positive attitude towards guidelines in general, but this attitude was not a predictor of guideline adherence. Conclusion: The good validity and reliability of our questionnaire can provide support for the accuracy of our findings. Multifaceted implementation strategies targeting the main barriers elicited from this study are required for addressing the lack of incentives, organizational resources, lack of confidence in the guideline, and time constraints.